E-hailing service satisfaction: a case study of students in a higher education institution in Perlis, Malaysia / Mohamad Niza Md Nor, Sabiroh Md Sabri and Najiah Filzah Mat Isa - Md Nor, Mohamad Niza; Md Sabri, Sabiroh; Mat Isa, Najiah Filzah (Universiti Teknologi MARA, Perlis, 2021)
E-hailing is an online transportation administration recognised as the travellers’ top pick in the transportation industry, including collaboration among clients and service providers. As clients now are more informed and can decide to choose any service provider they prefer, the e-hailing companies are obligated to fulfil and offer better support to their numerous clients, particularly for e-hailing administration. Keeping up consumer loyalty is vital for e-hailing’s specialist organisations to support upper hands. This research aims to investigate the role of safety and security, price, convenience and accessibility and whether they affect e-hailing service satisfaction. This research adopted a quantitative research methodology using a survey approach. Data was collected from 276 e-hailing services customers from higher learning institutions using an online survey. Data were analysed using the Statistical Package of Social Sciences (SPSS), and a few analyses were carried out, such as descriptive analysis, correlations and regression analysis. The results have shown that all factors have somehow affected e-hailing service satisfaction. This result will provide understanding to ridesharing service providers and can be used to improve their services by looking at the most and least influencing customer satisfaction. In the future, researchers could include diverse variables to study the customer satisfaction of e-hailing services in Malaysia.